Management of glucocorticoid-induced osteoporosis. - Rizzoli, R; Adachi, J; Cooper, C; Dere, W; Devogelaer, J; Diez-Perez, A; Kanis, J; Laslop, A; Mitlak, B; Papapoulos, S; Ralston, S; Reiter, S; et al. (2012)
This review summarizes the available evidence-based data that form the basis for therapeutic intervention and covers the current status of glucocorticoid-induced osteoporosis (GIOP) management, regulatory requirements, and risk-assessment options. Glucocorticoids are known to cause bone loss and fractures, yet many patients receiving or initiating glucocorticoid therapy are not appropriately evaluated and treated. An European Society for Clinical and Economic Aspects of Osteoporosis and Osteoarthritis workshop was convened to discuss GIOP management and to provide a report by a panel of experts. An expert panel reviewed the available studies that discussed approved therapeutic agents, focusing on randomized and controlled clinical trials reporting on bone mineral density and/or fracture risk of at least 48 weeks' duration. There is no evidence that GIOP and postmenopausal osteoporosis respond differently to treatments. The FRAX algorithm can be adjusted according to glucocorticoid dose. Available antiosteoporotic therapies such as bisphosphonates and teriparatide are efficacious in GIOP management. Several other agents approved for the treatment of postmenopausal osteoporosis may become available for GIOP. It is advised to stop antiosteoporotic treatment after glucocorticoid cessation, unless the patient remains at increased risk of fracture. Calcium and vitamin D supplementation as an osteoporosis-prevention measure is less effective than specific antiosteoporotic treatment. Fracture end-point studies and additional studies investigating specific subpopulations (pediatric, premenopausal, or elderly patients) would strengthen the evidence base and facilitate the development of intervention thresholds and treatment guidelines.